“Ten sam odwieczny wróg niebezpieczny.” The Universal Dimension of Tuwim’s Satire - Sidoruk, Elżbieta (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2020)
In the article, the author analyses the satirical works by Julian Tuwim published in his poetic collections. By indicating the strong bonds between poetry and satire in the poet’s works, the author explains the phenomenon of the unwavering topicality of Tuwim’s satire having generalising ambitions. She has considered the poet’s masterful combination of the poetic perspective with the attitude of a satirist as a factor which enables the generalisation of the critical diagnosis. However, she argues that the universal dimension of his wide-scope satirical works is mainly determined by the poet’s worldview-based horizons, which constituted the point of reference for his critical evaluation of the existing social reality, which exposed the destructive influence of a community on an individual. She also stated that he was able to peer deep into the mentality of the mindless members of the “tyrannous community” by virtue of his distance towards himself, in turn being the result of his sense of the absurdity of his own existence.